The Impact of Climate Variability and Adaptive Mechanisms of Community Farmers in Dry Climates Areas (The Case In Village Boronubaen And Taunbaen Timur Villages, Timor Tengah Utara District, East Nusa Tenggara) - Kumala Putri, Eka Intan; K Pandjaitan, Nurmala (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTClimate variability led to a number of risks to the agricultural production process and the risk of shocks to the livelihood systems, which ultimately impat on the resilience of households farmer. The purpose of the research: (1) identify the impact of climate variability on regional farms and farmer households, 2) the ways to anticipate and type of adaptive response of households farmer as effort to survive, 3) the direction change of the socio-economic, institutional and socio-ecological that accompany the adaptation process at household and community farmerslevel, and 4) to formulate suggestionthe adaptation mechanisms of households farmerin response the climate variability, which impacts on food security temporarily. The results showed in 2015, 2nd study areas is long drought.The Changes in productivity of rice crops due to climate variability in the Taunbaen Timurvillagehigher than Boronubaenvillage. The condition is supported by calculations Livelihood Vulnerability Index (LVI) showed household farmers in the Taunbaen Timur is more vulnerable than Boronubaen village household farmers. Food insecurity in the two villages is not only due to drought and pests, but also due to the high dependence on rice, making farming community poorer. To improve food security and resilience of householdfarmers income, need to increase public physical capital.Keywords: climate variability, vulnerability, resilience, food insecurity, livelihood.ABSTRAKVariabilitas iklim menyebabkan sejumlah risiko terhadap proses produksi pertanian dan risiko guncangan pada sistem penghidupan, yangakhirnya berdampak pada resiliensi rumahtangga petani. Tujuan penelitian yaitu (1) mengidentifikasidampak variabilitas iklim pada kawasanusahatani dan rumahtangga petani, 2)cara-cara mengantisipasi dan tipe respons adaptif rumahtangga petani dalam upaya bertahan hidup, 3) arah perubahan sistem sosio-ekonomi, kelembagaan dan sosio-ekologi yang menyertai proses adaptasi di tingkat rumahtangga dan komunitas petani, dan 4) memformulasi usulan mekanisme adaptasi rumahtangga petani dalam merespon variabilitas iklim, yang berdampak terhadap ketahanan pangan temporer. Hasil penelitian menunjukkan pada tahun 2015, ke-2 desa penelitian, mengalami kekeringan yang cukup panjang. Perubahan produktivitas tanaman padi akibat variabilitas iklim di Desa Taunbaen Timur lebih tinggi daripada di Desa Boronubaen. Kondisi tersebut didukung oleh perhitungan Livelihood Vulnerability Index (LVI) menunjukkan petani di Desa Taunbaen Timur lebih rentan dari pada petani Kelurahan Boronubaen terhadap variabilitas iklim. Kerawanan pangan di dua desa penelitian bukan hanya disebabkan oleh kekeringan dan hama penyakit, tetapi juga akibat ketergantungan beras yang tinggi, membuat komunitas petani semakin miskin.Untuk meningkatkan ketahanan pangan dan resiliensi nafkah rumahtangga petani, perlu peningkatan modal fisik yang bersifat publik.Kata kunci: variabilitas iklim, kerentanan, resiliensi, kerawanan pangan, nafkah.